Cytotoxicity assessment of α helix Antarctic yeast oriented antifreeze peptide (Afp1m) on M. dunni (Clone III8C) cells - Khan, Muhammad Shuaib; Abdul Rahman, Mohd Basyaruddin; Abu Bakar, Mohd Zuki; Noordin, Mohammed Mustapha; Ullah, Shakeeb; Abdul Abubakar, Adamu; Rehman, Saifur; Saddiqua, Aisha; Mohammad Yusof, Loqman (Universiti Putra Malaysia Press, 2024)
In order to assess the cytotoxic effects of the cryoprotectant helix Antarctic yeast-orientated antifreeze peptide Afp1m on normal mouse skin fibroblasts, an in vitro model was developed for cytotoxicity assessment. In order to evaluate the cytotoxic effects of Afp1m, the cells of M. dunni (Clone III8C) were subjected to various amounts of Afp1m. The cell viability was assessed using MTT Assay (Tetrazolium dye MTT 3-(4, 5 dimethylthiazol-2-yl)-2, 5-10 diphenyltetrazolium bromide) against the positive control cells (Clone III8C) thatshowed 86.73 ± 6.92 % viability of cells (103.9 ± 6.56 %, 104.3 ± 5.13%, 100.9 ± 1.71%, 102.8 ± 1.24%, and 100.00 ± 0.0%). At 24, 48, and 72 hr, retarded development was noted in 10 mg/mL Afp1m. Development was observed, albeit more slowly than in the positive control and treated with lesser concentrations. The findings of this work indicate that Afp1m exhibits cryoprotective properties without inducing toxicity when used for the cryopreservation of M. dunni (Clone III8C) cells. were cul t ured wi t h 10% FBS (Foet al Bovine Serum) using an Elisa reader and in medium containing various amounts (10, 5, 2, 1 and 0.5 mg/mL) of Afp1m, the control group (10% FBS) displayed varying survival percentages (78.86 ± 10.17%, 88.38 ± 3.19%, 88.75 ± 7.19 %, 90.61 ± 7.11%, 91.19 ± 4.52%, and 100.00 ± 0.0 %) throughout 24 hr. At 72 hr of treatment, the cell viability scores of Afp1m at 5, 2, 1, and 0.5 mg/mL were significantly higher (p<0.05) than those of 10mg/mL, which showed 86.73 ± 6.92 % viability of cells (103.9 ± 6.56 %, 104.3 ± 5.13%, 100.9 ± 1.71%, 102.8 ± 1.24%, and 100.00 ± 0.0%). At 24, 48, and 72 hr, retarded development was noted in 10 mg/mL Afp1m. Development was observed, albeit more slowly than in the positive control and treated with lesser concentrations. The findings of this work indicate that Afp1m exhibits cryoprotective properties without inducing toxicity when used for the cryopreservation of M. dunni (Clone III8C) cells.